THE CONCEPT OF "A REAL WOMAN" IN DAGESTAN PERCEPTION - Gimbatova, M B (History, Archeology and Ethnography of the Caucasus, 2015)
The article deals with the concept of real woman, in this regard the author analyzes her role and status in the traditional Dagestan society, her participation in public life, education, access to management, her place in the public space of the society, and her rights and freedoms in the area of family law.